Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1111/j.1399-5618.2012.01015.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional neuroanatomy of bipolar disorder: structure, function, and connectivity in an amygdala–anterior paralimbic neural system

Abstract: Objectives-In past decades, neuroimaging research in bipolar disorder has demonstrated a convergence of findings in an amygdala-anterior paralimbic cortex neural system. This paper reviews behavioral neurology literature that first suggested a central role for this neural system in the disorder and the neuroimaging evidence that supports it.Methods-Relevant articles are reviewed to provide an amygdala-anterior paralimbic cortex neural system model of bipolar disorder, including articles from the fields of beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
110
1
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(128 citation statements)
references
References 225 publications
13
110
1
4
Order By: Relevance
“…A better understanding of the cerebral mechanisms and impact of mood switching in BD is crucial in order to develop or improve treatments for this disorder. Functional neuroimaging studies in patients with BD have evidenced changes in limbic and prefrontal networks relative to healthy people (for reviews, see Blond et al, 2012;, suggesting anomalies in neural circuits involved in affective regulation that are potentially responsible for emotional homeostasis or its loss . However, few studies have sought to determine a neural signature of BD in different mood states.…”
Section: Introductionmentioning
confidence: 99%
“…A better understanding of the cerebral mechanisms and impact of mood switching in BD is crucial in order to develop or improve treatments for this disorder. Functional neuroimaging studies in patients with BD have evidenced changes in limbic and prefrontal networks relative to healthy people (for reviews, see Blond et al, 2012;, suggesting anomalies in neural circuits involved in affective regulation that are potentially responsible for emotional homeostasis or its loss . However, few studies have sought to determine a neural signature of BD in different mood states.…”
Section: Introductionmentioning
confidence: 99%
“…Essa variação nos resultados obtidos em adultos pode ser justificada pelos efeitos neurotrófi-cos de fármacos utilizados na estabilização do humor, pelas variações genéticas de cada indivíduo ou pelos aspectos relacionados ao neurodesenvolvimento. De fato, alguns estudos que utilizaram PET ou SPECT demonstraram anormalidades funcionais da amígdala -hipermetabolismo na fase depressiva em alguns estudos, versus hipometabolismo em outros, nas fases tanto de depressão quanto de mania 26 . Por outro lado, vários estudos que utilizaram RNMf e mediram resposta a estímulos emocionais positivos utilizando tarefas cognitivas sem valência emocional descreveram hiperatividade da amígdala apenas na fase de mania 27 .…”
Section: Lobo Temporalunclassified
“…Por outro lado, vários estudos que utilizaram RNMf e mediram resposta a estímulos emocionais positivos utilizando tarefas cognitivas sem valência emocional descreveram hiperatividade da amígdala apenas na fase de mania 27 . Os estudos de RNM que mediram o hipocampo encontraram resultados muito variáveis, o que pode ser explicado em parte por variações genéticas (carreamento do alelo Met, associado a menores volumes hipocampais), efeitos de tratamento (uso de lítio, associado a aumento do volume hipocampal) ou hormô-nios sexuais 26 . Entretanto, uma menor concentração de NAA no hipocampo de pacientes adultos eutímicos foi documentada em uma metanálise 20 .…”
Section: Lobo Temporalunclassified
“…Emotional dys-regulation is a hallmark feature of pediatric BD. One of the bestreplicated finding in pediatric BD is an impaired ability in processing emotions (including emotion labeling deficits), assessed through face processing paradigms (for reviews, see Blond et al 2012;Chen et al 2011;Delvecchio et al 2012;Houenou et al 2011;Kupferschmidt and Zakzanis 2011;Strakowski et al 2012). In addition to impaired emotional processing, studies have also revealed cognitive control deficits in pediatric BD (for a review, see Passarotti and Pavuluri 2011).…”
Section: Clinical Presentation and Behavioralmentioning
confidence: 99%
“…Together, these difficulties in emotional processing may contribute to the social impairment commonly observed in BD, since the ability to read social cues and facial expressions is essential for adaptive social functioning. fMRI findings: Research examining the neural circuitry mediating face emotion processing in BD implicates dysfunction in the fronto-limbic-striatal network (for reviews, see Blond et al 2012;Chen et al 2011;Delvecchio et al 2012;Houenou et al 2011;Kohler et al 2011;Kupferschmidt and Zakzanis 2011;Pavuluri and Passarotti 2008;Strakowski et al 2012). Abnormalities in amygdala function during face emotion processing are observed consistently in both children (for a review, see Pavuluri and Passarotti 2008) and adults with BD (for a review, see Strakowski et al 2012).…”
Section: Face Emotion Processingmentioning
confidence: 99%